Identification of Streptococcus sanguinis genes producing biofilm from gingivitis: Streptococcus sanguinis genes - Hassan, Pakhshan Abdullah; Hameed Saeed, Chiman; Rashid, Sirwan Ahmed; Sorchee, Sawsan Mohammed; Shareef, Suhayla Hamad (Cellular and Molecular Biology, 2022)
Streptococcus sanguinis is a teeth commensal frontier colonizer and among the most common species in the oral biofilm. Dental plaque, caries, and gingivitis/periodontitis are caused by dysbiosis of oral flora. A biofilm assay was developed to investigate biofilm formation in S. sanguinis using the microtiter plate, tube, and Congo red agar methods in order to identify causing bacteria and determine responsible genes. Three genes, including pur B, thr B, and pyre E, were suspected of playing a role in forming in vivo biofilms in S. sanguinis. The present study shows these genes to be responsible for increased biofilm formation in gingivitis patients.